Sensory evaluation of chocolates in children - Lopez R., Luz (2001)
In the present survey, factors influencing chocolate acceptability by kids between 6-10 years old have been identified through, the evaluation of products shape, color and savor. It was determined that the child population showed their preference for a milk covering and an oval shape in chocolates.